Skewed endosomal RNA responses from TLR7 to TLR3 in RNase T2-deficient macrophages. (23rd June 2021) - Liu, Kaiwen; Sato, Ryota; Shibata, Takuma; Hiranuma, Ryosuke; Reuter, Tatjana; Fukui, Ryutaro; Zhang, Yun; Ichinohe, Takeshi; Ozawa, Manabu; Yoshida, Nobuaki; Latz, Eicke; Miyake, Kensuke
Abstract: RNase T2, a ubiquitously expressed RNase, degrades RNAs in the endosomal compartments. RNA sensors, double-stranded RNA (dsRNA)-sensing Toll-like receptor 3 (TLR3) and single-stranded RNA (ssRNA)-sensing TLR7, are localized in the endosomal compartment in mouse macrophages. We here studied the role of RNase T2 in TLR3 and TLR7 responses in macrophages. Macrophages expressed RNase T2 and a member of the RNase A family RNase 4. RNase T2 was also expressed in plasmacytoid and conventional dendritic cells. Treatment with dsRNAs or type I interferon (IFN) up-regulated expression of RNase T2 but not RNase 4. RNase T2-deficiency in macrophages up-regulated TLR3 responses but impaired TLR7 responses. Mechanistically, RNase T2 degraded both dsRNAs and ssRNAs in vitro, and its mutants showed a positive correlation between RNA degradation and the rescue of altered TLR3 and TLR7 responses. H122A and C188R RNase T2 mutations, not H69A and E118V mutations, impaired both RNA degradation and the rescue of altered TLR3 and TLR7 responses. RNase T2 in bone marrow-derived macrophages was broadly distributed from early endosomes to lysosomes, and colocalized with the internalized TLR3 ligand poly(I:C). These results suggest that RNase T2-dependent RNA degradation in endosomes/lysosomes negatively and positively regulates TLR3 and TLR7 responses, respectively, in macrophages. Abstract : RNase T2 has opposite effects on TL3 versus TLR7 responses